Cover Picture: Biotechnology Journal 9/2018. Issue 9 (3rd September 2018) - Unknown
Abstract : Metabolic engineering requires an extensive search across the genetic landscape. However, this search (especially in yeast) can be accelerated using new advances in multiplexed dCas9 gene regulation. In article1700582, Hal. S. Alper and co‐workers develop a method termed Ligation Extension of gRNA Operons (LEGO) to construct multiplexed gRNA combinations from modular and easily‐synthesized gRNA bricks.